The Effects of Fibromyalgia Syndrome on Physical Function and Psychological Status of Pregnant Females - Hakan GENÇ,; Melahat ATASEVER,; Burcu DUYUR ÇAKIT,; Murat SEVAL,; Acar KOÇ, (Archives of Rheumatology, 2017)
Objectives: This study aims to investigate the frequency and most common symptoms of fibromyalgia syndrome (FS) among pregnant females and determine the impacts of FS on physical functioning and psychological status. Patients and methods: A total of 360 pregnant females (mean age 26.5 years, range 19 to 42 years) were included. The subjects were divided into two groups in terms of having (FS group; n=136; mean age 27 years; range 19 to 41 years) or not having FS (control group; n=224; mean age 26.5 years; range 20 to 42 years). The impact of FS on physical functions was evaluated using Fibromyalgia Impact Questionnaire. Psychological statuses of the subjects were evaluated using State-Trait Anxiety Inventory, Wijma Delivery Expectancy/Experience Questionnaire, and Beck Depression Inventory. Results: Low back pain was the most common complaint while fatigue was the most common symptom in FS group. FS group had higher levels of pain and physical disability (p<0.001) and also higher values of anxiety, fear of childbirth, and depression (p<0.001, for all values) compared to control group. Symptom severity and physical function scores were significantly correlated with increased levels of pain, depression, anxiety, and fear of childbirth (p<0.001, for all values). Conclusion: Fibromyalgia syndrome is common among pregnant females. The existence of FS in pregnancy is a severe factor contributing to maternal stress, anxiety, and depression. Therapeutic measures for fibromyalgia syndrome should be well-established to support healthy pregnancy and good child health outcome.